1986
DOI: 10.1007/bf02555195
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the intravenous administration of magnesium sulfate on corrected serum calcium level and nephrogenous cyclic AMP excretion in normal human subjects

Abstract: The effect of intravenous magnesium sulfate infusion on corrected serum calcium level and parathyroid function assessed by determination of nephrogenous cAMP (NcAMP) excretion were studied in normal human subjects. Significant hypermagnesemia induced by the magnesium sulfate infusion for 120 minutes was accompanied by a gradual and progressive decrease in the corrected serum calcium level. NcAMP excretion fell rapidly, reaching a nadir between 60 and 120 minutes after the infusion began, and after that rose ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
16
0

Year Published

1988
1988
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 32 publications
3
16
0
Order By: Relevance
“…4,5 This effect was attributable to magnesium and not sulfate. 6 Attempts have been made to localize the segment where urinary magnesium could mediate its effect on calcium reabsorption in different animal models. Metabolic experi-…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…4,5 This effect was attributable to magnesium and not sulfate. 6 Attempts have been made to localize the segment where urinary magnesium could mediate its effect on calcium reabsorption in different animal models. Metabolic experi-…”
mentioning
confidence: 99%
“…4,5 This effect was attributable to magnesium and not sulfate. 6 Attempts have been made to localize the segment where urinary magnesium could mediate its effect on calcium reabsorption in different animal models. Metabolic experi-ments confirmed that calciuria can be increased by intravenous magnesium infusion in dogs with normal or reduced kidney function, 7 but stop-flow experiments did not precisely identify the segment involved.…”
mentioning
confidence: 99%
“…It is biochemically or ultrastructurally reported that Mg decreases the activity of the PTH (Altenahr and Leonhardt, 1972;Cholst et aL, 1984;Suzuki et aL, 1986;Utsumi et aL, 1997). In the PTG of the 1.2G group the rER had significantly increased cornpared with that of the control group.…”
Section: Discussionmentioning
confidence: 92%
“…On the other hand, it is well known in the biochemical or morphological study that magnesium (Mg) plays an important role in the regulation of parathyroid hormone secretion as well as calcium (Altenahr and Leonhardt, 1972;Cho1st et al , 1984;Suzuki et aL, 1986;Utsumi et aL, 1997).…”
mentioning
confidence: 99%
“…Radde et aL (1968) have shown in the rat that the secondary hypocalcemia following Mg load is due to stimulation of calcitonin secretion by an elevated Mg level , and that the persistence of hypocalcemia in animals bearing functioning parathyroid glands is due to suppression of PTH secretion. Suzuki et al, (1986) have reported in normal human subjects that the hypocalcemia caused by Mg is mainly due to the renal calcium loss, and the suppressive effect of Mg on parathyroid function may be only partially involved in the early phase of the hypocalcemia. The present in vivo study of the hamster demonstrates that the serum calcium level significantly decreased at 30 min and 1 hr after Mg injection, and that the hamster reacts similarly, developing hypocalcemia after Mg injection.…”
Section: Stereological Analysis Of the Parathyroid Glandmentioning
confidence: 99%